Microbial Volatile Organic Compounds: Applications and Future Prospects - Kumar, Vikas; Singh, Manoj; Devi, Ashwanti; Rani, Kavita; Kumar, Amit; Kumar, Sunil; Sharma, Pooja; Sharma, Anil K (Asian Journal of Biological and Life Sciences)
Microbial volatile organic compounds (MVOCs) are organic compounds having low molecular mass (less than 300 Da) and high vapor pressure due to low boiling point. Microorganisms produce a plethora of volatile compounds that can play a very crucial role in intra- and inter-kingdom interactions. Many volatile organic compounds (VOCs) secreted by microbes associated with soil and plants have been described to be involved in microbial communications. A considerable body of opinion indicates that MVOCs have potential to be utilized as a beneficial and good sustainable approach for diverse areas including agriculture, industrial and health sector. They can induce plant defense systems and inhibit the development of diverse plant pathogens.
Keywords: Inter-kingdom interactions; Microbial communications; Microbial volatile organic compounds; Plant pathogens; Sustainable strategy